Conductive ink
The conductive ink composition, featuring fine silver particles, specific amines, polymers, and binders, addresses the challenge of substrate damage in film device manufacturing by ensuring adhesion and conductivity at lower temperatures.
Patent Information
- Application Number
- JP2024515720
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-31
- Filing Date
- 2024-03-04
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2044-03-04
AI Technical Summary
In the manufacturing of film devices, the repeated application of conductive ink and subsequent heat treatment to sinter silver fine particles can damage substrates with low heat resistance, and there is a need for a method that ensures good conductivity and adhesion at lower temperatures.
A conductive ink composition containing fine silver particles, an amine with a hydroxyl group, a polymer with an acidic group, and a binder, which is heated at a lower temperature to ensure adhesion to the substrate and then sintered at a higher temperature to achieve good conductivity.
The proposed conductive ink achieves good conductivity and adhesion to substrates with low heat resistance, reducing the risk of substrate damage during the manufacturing process of film devices.
Smart Images

Figure 0007649425000001 
Figure 0007649425000002
Abstract
Description
[Technical field]
[0001] The present invention relates to conductive inks. This application claims priority to Japanese Application No. 2023-057820, filed on March 31, 2023, and incorporates by reference all of the contents of said Japanese application. [Background technology]
[0002] By reducing the particle size to nanometer size, silver particles can be sintered at low temperatures by lowering their melting point. By utilizing this property, conductive inks containing silver particles can be used as materials for drawing electrical wiring on substrates.
[0003] Regarding conductive inks used in such fields, Patent Document 1 describes a method for producing silver nanoparticles by reacting a thermally decomposable silver compound (a) with an amine compound (b) that forms a complex, in which an amino alcohol that (i) has a linear structure, (ii) has one amino group and one hydroxyl group at each end of the linear molecule, and (iii) has one or more ether bonds within the linear structure is used as the amine compound. Patent Document 1 describes that by using such a specific amino alcohol, silver nanoparticles having a wide distribution and relatively large particle size can be easily obtained, and that silver nanoparticles in the large particle size range of 200 to 500 nm can be particularly easily synthesized.
[0004] Furthermore, Patent Document 1 describes a method for producing a silver coating composition, in which the obtained silver nanoparticles are dispersed in an organic solvent and an organic binder is further added. Cited document 1 also describes that a silver coating composition containing silver particles with controlled particle size can be sintered even at low temperatures below 150° C., and that the resulting sintered body exhibits a low resistance value close to that of bulk silver. Cited document 1 also describes that this silver coating composition is a material that can be used to form thick silver wiring of several to several tens of μm on a plastic substrate with relatively low heat resistance, such as PET or polypropylene, by a printing method such as screen printing. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2021-105218 A Summary of the Invention [Problem to be solved by the invention]
[0006] A conductive ink containing silver fine particles can be used as a material for forming electrical wiring on a substrate made of a resin film, etc. Therefore, it is used for forming electrical wiring that constitutes a film device. When forming electrical wiring on a base material, the electrical wiring is formed through at least a step of printing a conductive ink on a substrate and a step of heating at a predetermined temperature to sinter the silver particles. In the manufacturing method of the film device, the step of applying the conductive ink may be performed multiple times depending on the design of the film device. For example, when manufacturing a film device having electrical wiring on both sides of a substrate, a step of applying the conductive ink to one side of the substrate and a step of applying the conductive ink to the other side of the substrate may be performed separately.
[0007] In this way, when the step of applying the conductive ink is performed multiple times, a heat treatment for sintering the silver particles may be performed each time the conductive ink is applied to complete the electrical wiring. However, if the heat treatment for sintering the silver particles is performed each time the conductive ink is applied, the substrate is susceptible to damage by heat. Therefore, in the manufacturing method of the film device, it is desirable to perform the heat treatment at a low temperature and for a short time as possible.
[0008] In addition, for example, a roll-to-roll method may be adopted as a method for manufacturing a film device. In a manufacturing method using the roll-to-roll method, a conductive ink may be applied to an unwound substrate, the substrate may be wound into a roll, and then, in a separate process, a conductive ink may be applied again to the unwound substrate. In this case, the conductive ink applied to the substrate needs to be in close contact with the substrate. If the conductive ink is not in close contact with the substrate, the applied conductive ink may migrate to the surface of the substrate opposite to the ink-applied surface when the substrate is wound into a roll. Therefore, in order to make the applied conductive ink adhere to the substrate, a heat treatment may be performed to sinter the silver fine particles. However, if a heat treatment is performed to sinter the silver particles every time the conductive ink is applied, the base material becomes susceptible to damage from heat, as described above.
[0009] In light of this situation, in order to reduce heat damage to the substrate in a manufacturing method for film devices that involves applying conductive ink multiple times, we considered a method in which, after each application of conductive ink, a heating treatment is performed at a temperature lower than the temperature at which the silver microparticles are sufficiently sintered, so that the conductive ink adheres to the substrate to the extent that it does not peel off, and after completing the process of applying conductive ink multiple times, the silver microparticles are sufficiently sintered in a single heating treatment.
[0010] Therefore, we investigated a conductive ink that can exhibit good conductivity and also has excellent adhesion to the substrate by adhering it to the substrate through heat treatment at a temperature lower than the temperature at which the silver microparticles are sintered, and then baking it at a specified temperature. As a result, the present inventors discovered a novel conductive ink that satisfies these requirements, and completed the present invention. It was thought that it would be difficult to ensure sufficient adhesion to the substrate with the silver coating composition described in Patent Document 1. [Means for solving the problem]
[0011] (1) The conductive ink of the present invention is a conductive ink containing silver fine particles, an amine, a polymer having an acidic group, and a binder, The average primary particle diameter of the silver fine particles is 10 nm or more and 30 nm or less, The content of the silver fine particles is 20% by mass or more and 65% by mass or less, The amine includes an amine having a hydroxyl group, The binder includes a blocked isocyanate and / or a polyurethane.
[0012] The conductive ink is subjected to a heat treatment (first baking treatment) at a temperature lower than the heating temperature for sintering the silver particles (for example, about 100°C) to become a coating film that ensures adhesion to the substrate. By subjecting the conductive ink to a predetermined heat treatment (second baking treatment) at, for example, 150° C., a sintered body of silver is formed, forming a conductive film having good conductivity. Therefore, the conductive ink can be suitably used for forming wiring in a film device, for example.
[0013] (2) The conductive ink of (1) above preferably contains, as the amine having a hydroxyl group, at least one selected from 2-(2-aminoethoxy)ethanol, 2-(2-aminoethylamino)ethanol, 2-[2-(2-aminoethoxy)ethoxy]ethanol, and monoethanolamine. (3) The conductive ink of (1) or (2) above preferably further contains an alkoxyamine as the amine. Conductive inks having these compositions are suitable for forming a coating film that ensures adhesion to the substrate in the first baking treatment, and for forming a conductive film with good conductivity after the baking treatment. Effect of the Invention
[0014] The conductive ink can form a coating film that ensures adhesion to the substrate by heating at a temperature lower than the temperature at which the silver particles are sintered. In addition, the silver particles can be sintered by heating at about 150° C. to form a conductive film that has good conductivity and adhesion to the substrate. Since the conductive film can be formed by heating at about 150° C., a substrate made of a material with poor heat resistance, such as a resin film, can also be used as the substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention will be described. A conductive ink according to an embodiment of the present invention contains silver particles, an amine, a polymer having an acidic group, and a binder. The silver particles are sintered by heating to form a conductive film. The amine and the polymer having an acidic group adhere to the surface of the silver fine particles and function as a dispersant for dispersing the silver fine particles. The binder contributes to improving the adhesion between the conductive film and the substrate on which the conductive film is formed.
[0016] The conductive ink has an average primary particle diameter of the silver microparticles of 10 nm or more and 30 nm or less, a content of the silver microparticles of 20 mass % or more and 65 mass % or less, contains an amine having a hydroxyl group as the amine, and contains at least one of a blocked isocyanate and a polyurethane as the binder.
[0017] The conductive ink is used for forming wiring in a film device. In particular, the conductive ink can be suitably used in a method for producing a film device having a step of applying the conductive ink multiple times. In this case, a first baking is performed for each step of applying the conductive ink to adhere the coating film of the conductive ink to the substrate, and after performing the step of applying the conductive ink multiple times, the first-baked conductive ink is subjected to a second baking, thereby allowing the silver fine particles to be sufficiently sintered.
[0018] In this specification, the heating applied to the conductive ink, regardless of the temperature, is also referred to as baking. In this specification, the heating step for drying the conductive ink to form a coating film is also referred to as the first baking step, and the heating step for sintering the silver particles contained in the conductive ink to form a conductive film exhibiting sufficient conductivity is also referred to as the second baking step. Note that in the first baking step, some of the silver particles may be sintered.
[0019] Since the conductive ink has the above-mentioned composition, the first baking can be carried out at about 100°C, and the second baking can be carried out at about 150°C.
[0020] The reason for this is speculated as follows. When the above-mentioned conductive ink is baked at around 100°C, it is believed that the coating film formed contains enough dispersant (amines with hydroxyl groups and / or polymers with acidic groups) to form appropriate intermolecular forces or chemical bonds (collectively referred to as intermolecular forces, etc.) with the binder or the surface of the substrate, thereby ensuring adhesion to the substrate. It is also assumed that when the conductive ink is baked at about 150° C., the conductive film formed has sufficient conductivity because the dispersant is removed to the extent that it does not inhibit the sintering of the silver particles. It is also assumed that when the conductive ink is baked at about 150° C., the dispersant is not completely removed, and intermolecular forces are formed between the binder (blocked isocyanate with the protective group removed and / or polyurethane) and the surface of the substrate, so that adhesion to the substrate is maintained. In this specification, when a binder in which intermolecular forces or the like are formed between the binder and a substrate or a dispersant is mentioned, this binder is a concept that includes blocked isocyanates from which the protecting groups have been removed.
[0021] <Silver fine particles> The average primary particle diameter of the fine silver particles is 10 nm or more and 30 nm or less. When a conductive ink is used on a substrate having relatively low heat resistance, such as a resin film, it is required to sinter at a low baking temperature (for example, about 150° C.). Since the average primary particle diameter of the silver particles in the conductive ink according to the embodiment of the present invention is within the above range, sintering of the silver particles proceeds sufficiently even at a baking temperature of about 150° C., and a conductive film having good conductivity can be formed. On the other hand, if the average primary particle diameter of the silver fine particles is less than 10 nm, the amount of dispersant required to maintain the ink properties is large, and the conductive film formed may have insufficient conductivity or may be prone to cracking when fired at 150° C. Also, if the average primary particle diameter of the silver fine particles is greater than 30 nm, the silver fine particles are not sintered sufficiently at 150° C., and in this case too, the conductive film formed is likely to have insufficient conductivity.
[0022] The average primary particle size of the silver particles is determined by number average. Specifically, the silver particles are observed at a magnification of 200,000 times using a scanning electron microscope (S-4800 manufactured by Hitachi Ltd.), the primary particle size of the particles contained in the captured image is measured using image analysis software (WinROOF manufactured by MITANI CORPORATION), and the number average is calculated.
[0023] The content (concentration) of the silver particles in the conductive ink is 20% by mass or more and 65% by mass or less. If the content of the silver particles is 20% by mass or more, it is suitable for forming a conductive film with high conductivity.If the content of the silver particles is 65% by mass or less, the viscosity does not become too high and handling is easy. The content of the fine silver particles is preferably 25% by mass or more and 40% by mass or less.
[0024] The conductive ink may contain at least one type of metal particles other than silver in addition to the silver fine particles. By blending the metal particles other than silver, migration is less likely to occur in the conductive film formed by the conductive ink. As the metal other than silver, a metal whose ionization series is more noble than hydrogen is preferable. As the metal whose ionization series is more noble than hydrogen, gold, copper, platinum, palladium, rhodium, iridium, osmium, ruthenium, and rhenium are preferable, and gold, copper, platinum, and palladium are more preferable. These metals may be used alone or in combination of two or more kinds. The average primary particle size of the particles of a metal other than silver is preferably 10 nm or more and 30 nm or less.
[0025] <Amine> The conductive ink contains an amine having a hydroxyl group. Amines having a hydroxyl group are suitable as amines that generate intermolecular forces or chemical bonds between binders (blocked isocyanates and / or polyurethanes from which the protective groups have been removed) and substrates. A hydroxyl-containing amine has at least two polar groups (an amino group and a hydroxyl group) in one molecule, and therefore can act as a dispersant to disperse silver particles and generate intermolecular forces and chemical bonds between the binder and the base material. In addition, amines with hydroxyl groups have higher boiling points than alcohols with comparable molecular weights or amines without hydroxyl groups, so they are less likely to disappear completely during the first baking step and tend to remain in an appropriate amount.
[0026] The boiling point of the hydroxyl-containing amine is preferably 170° C. or higher. If the boiling point is 170° C. or higher, the hydroxyl-containing amine remains in the coating film to a suitable extent even after the first baking is performed at, for example, 100° C. Therefore, intermolecular forces and chemical bonds can be formed between the binder and the substrate, which can contribute to improving the adhesion between the coating film of the conductive ink and the substrate after the first baking. The boiling point of the amine containing a hydroxyl group is more preferably 220° C. or higher. The boiling point of the amine containing a hydroxyl group is preferably 250° C. or lower. In the present invention, the boiling point refers to the boiling point at 1 atmospheric pressure.
[0027] As the amine having a hydroxyl group, 2-(2-aminoethoxy)ethanol, 2-(2-aminoethylamino)ethanol, 2-[2-(2-aminoethoxy)ethoxy]ethanol, and monoethanolamine are preferred. The amine having a hydroxyl group may be used alone or in combination of two or more kinds.
[0028] The content (concentration) of the amine having a hydroxyl group is preferably 0.01% by mass or more and 2% by mass or less, which is suitable for achieving both the role of a dispersant for dispersing silver particles and the role of generating intermolecular forces between the binder and the base material. On the other hand, if the content of amine having a hydroxyl group is less than 0.01% by mass, the silver particles cannot be stably dispersed and may aggregate, and if it exceeds 2% by mass, the amount of amine having a hydroxyl group remaining after baking the conductive ink increases, and the conductivity of the formed conductive film may become insufficient.
[0029] The conductive ink preferably contains an alkoxyamine in addition to the amine containing a hydroxyl group. When an alkoxyamine is contained, the conductive ink containing silver particles has good low-temperature sintering properties. In addition, the size (primary particle diameter) of the silver particles is easily adjusted during the production of the conductive ink. For example, when silver particles are produced in the presence of an alkoxyamine, it is easy to narrow the particle size distribution of the silver particles or to reduce the size of the silver particles. The alkoxyamine is preferably an alkoxyamine having a carbon number of 6 or less. Here, the carbon number of the alkoxyamine is the carbon number not including the alkoxy group, which is a functional group.
[0030] Examples of the alkoxyamine include 2-methoxyethylamine, 3-methoxypropylamine, 3-ethoxypropylamine, 3-propoxypropylamine, 3-butoxypropylamine, 2-ethoxypropylamine, 3-isopropoxypropylamine, 2-methoxy-2-methylpropylamine, and N-(3-methoxypropyl)propane-1,3-diamine.
[0031] The conductive ink may contain an amine other than an amine having a hydroxyl group and an alkoxyamine.
[0032] <Polymer having acidic groups> The conductive ink contains a polymer having an acidic group. The polymer having an acidic group may be a homopolymer or a copolymer. The polymer having an acidic group can function as a dispersant for dispersing the fine silver particles and can also function as a catalyst for generating intermolecular forces between the polymer and the binder or substrate.
[0033] The content (concentration) of the polymer having the acidic group is preferably 0.01% by mass or more and 2% by mass or less, which is suitable for achieving both the role of a dispersant for dispersing silver particles and the role of generating intermolecular forces between the polymer and the binder or base material. On the other hand, if the content of the polymer having an acidic group is less than 0.01% by mass, the silver particles cannot be stably dispersed and may aggregate, whereas if the content exceeds 2% by mass, a large amount of the polymer having an acidic group remains after sintering the silver particles, which may cause a loss of conductivity of the formed conductive film.
[0034] The above-mentioned polymer having an acidic group preferably has an acid value of 5 or more and 200 or less. When the acid value of the polymer having an acidic group is 5 or more, the polymer starts to adsorb to the fine silver particles, which are coordinated with amines and have a basic particle surface, through acid-base interaction.When the acid value is 200 or less, the polymer does not have an excessive number of adsorption sites, and is adsorbed to the fine silver particles in a suitable form.
[0035] The polymer having the acidic group is preferably one having a functional group derived from phosphoric acid as the acidic group. In this case, phosphorus (P) interacts with and attracts silver via oxygen (O), so the polymer having a functional group derived from phosphoric acid is suitable for adsorbing silver or a silver compound, and can ensure suitable dispersibility of silver particles with the minimum necessary amount of adsorption.
[0036] As the above-mentioned polymer having an acidic group, a commercially available product can be used. Commercially available products of the polymer having the above acidic group include, for example, DISPERBYK-102, DISPERBYK-106, DISPERBYK-110, DISPERBYK-111, DISPERBYK-118, DISPERBYK-140, DISPERBYK-142, DISPERBYK-145, DISPERBYK-180 (all manufactured by BYK Japan), SOLSPERSE 36000, SOLSPERSE 36600, SOLSPERSE 41000, SOLSPERSE 41090, SOLSPERSE 43000, SOLSPERSE 44000, SOLSPERSE 46000, SOLSPERSE Examples of such compounds include Disparlon 55000 (all manufactured by Lubrizol Japan), Disparlon 1831, Disparlon 1850, Disparlon 1860, Disparlon 2150, Disparlon PW-36, Disparlon DA-1200 (all manufactured by Kusumoto Chemical Industry), Floren AF-1000, Floren AF-1005, Floren G-700, and Floren GW-1500 (all manufactured by Kyoeisha Chemical Industry). These may be used alone or in combination of two or more.
[0037] <Binder> The binder is a blocked isocyanate and / or a polyurethane. The amine having a hydroxyl group as the dispersant has an amino group and a hydroxyl group in the molecule, and therefore the binder preferably has a polar group capable of forming a bond with the amino group and / or the hydroxyl group. In the blocked isocyanate, the polar group capable of forming a bond with an amino group or a hydroxyl group may be any group that appears when the protecting group is removed. Blocked isocyanates and polyurethanes from which the protecting groups have been removed form favorable intermolecular forces and chemical bonds with dispersants containing amines having hydroxyl groups and with substrates, and are likely to exhibit adhesion between the conductive film and the substrate.
[0038] <<Blocked isocyanate>> The binder is preferably a blocked isocyanate. A blocked isocyanate is an isocyanate compound (isocyanate component) in which the isocyanate group is protected with a blocking agent. The blocked isocyanate remains stable under normal conditions (when it is blended into a conductive ink and the conductive ink is not heated), and when it is heat-treated, the blocking agent dissociates and active isocyanate groups are regenerated.
[0039] The blocked isocyanate is a reaction product between an isocyanate compound and a blocking agent. The isocyanate compound may be any compound having an isocyanate group, and is preferably one having two or more isocyanate groups. The above isocyanate compound more preferably has two isocyanate groups. As the blocked isocyanate, a known blocked isocyanate can be used.
[0040] The blocked isocyanate is preferably a reaction product of an isocyanate compound having a hydrocarbon group and a plurality of isocyanate groups, such as an aliphatic polyisocyanate, an alicyclic polyisocyanate, or an aromatic polyisocyanate (hereinafter also referred to as a hydrocarbon polyisocyanate), with a blocking agent.
[0041] Examples of the aliphatic polyisocyanate include 1,4-tetramethylene diisocyanate, 1,5-pentamethylene diisocyanate, 1,6-hexamethylene diisocyanate (HDI), 2,2,4-trimethylhexamethylene diisocyanate, and their isocyanurate modified products, prepolymer modified products, biuret modified products, and allophanate modified products.
[0042] Examples of the alicyclic polyisocyanate include isophorone diisocyanate (IPDI), 1,3-bis(isocyanatemethyl)-cyclohexane, 4,4'-dicyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, norbornane diisocyanate (NBDI), and their isocyanurate modified products, prepolymer modified products, biuret modified products, and allophanate modified products.
[0043] Examples of the aromatic isocyanate include tolylene diisocyanate (TDI), phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 1,5-naphthalene diisocyanate, xylylene diisocyanate (XDI), 4,4'-diisocyanate-3,3'-dimethylbiphenyl, 1,3-bis(2-isocyanate-2-propyl)benzene, and isocyanurate-modified, prepolymer-modified, biuret-modified, and allophanate-modified versions of these.
[0044] As the blocking agent, known blocking agents such as alkyl ketone oximes, phenols, alcohols, β-diketones, and lactams can be used. Specific examples of the blocking agent include methyl ethyl ketone oxime, ε-caprolactam, phenol, cresol, acetylacetone, diethyl malonate, isopropyl alcohol, tert-butyl alcohol, and maleic acid imide. As the blocking agent, dialkyl ketone oximes such as methyl ethyl ketone oxime, lactams such as ε-caprolactam, etc. are preferable, because they are suitable for producing blocked isocyanates having a dissociation temperature of 80° C. or higher and 150° C. or lower.
[0045] When the blocked isocyanate is a reaction product of a hydrocarbon polyisocyanate and a blocking agent, the hydrocarbon polyisocyanate is preferably an aliphatic polyisocyanate or an alicyclic polyisocyanate rather than an aromatic polyisocyanate. Aliphatic polyisocyanates and alicyclic polyisocyanates are not as reactive as aromatic isocyanates, and form an appropriate three-dimensional structure under the conditions of the second baking step in which the silver particles are sintered, so that the conductivity of the conductive film is less likely to be impaired.
[0046] Furthermore, the hydrocarbon polyisocyanate is preferably an aliphatic polyisocyanate rather than an alicyclic polyisocyanate, since aliphatic polyisocyanates are more likely to achieve both electrical conductivity and bending resistance. In the aliphatic polyisocyanate, the hydrocarbon group may be linear or may have a branched chain, but is preferably linear. When an aliphatic polyisocyanate having a linear hydrocarbon group is used as the aliphatic polyisocyanate, it is easy to ensure the flexibility of the conductive film formed by using the conductive ink. Hexamethylene diisocyanate is particularly preferred as the aliphatic polyisocyanate, as it is particularly suitable for ensuring good electrical conductivity and good bending resistance in the formed conductive film.
[0047] The dissociation temperature of the blocked isocyanate is preferably 110° C. or higher and 150° C. or lower, because the reaction easily proceeds in parallel with the sintering of the silver particles, and the blocked isocyanate can also be used by being applied to a substrate having low heat resistance. The dissociation temperature of the blocked isocyanate is measured by differential scanning calorimetry (DSC). Specifically, the temperature of the endothermic peak associated with the deprotection reaction of the blocked isocyanate measured by differential scanning calorimetry corresponds to the dissociation temperature of the blocked isocyanate. In this case, for example, a differential scanning calorimeter (DSC 3500 Sirius) manufactured by NETZSCH can be used as the differential scanning calorimeter.
[0048] As the blocked isocyanate, commercially available products can also be used. Commercially available examples of the blocked isocyanate include Takenate B-882N, Takenate B-890, Takenate B-7005 (all manufactured by Mitsui Chemicals, Inc.), Duranate MF-K60B, Duranate SBB-70P, Duranate SBN-70D, Duranate 17B-60P, Duranate E402-B80B, Duranate TPA-B80E, Duranate WM44-L70G (all manufactured by Asahi Kasei Corporation), and Coronate BI-301 (manufactured by Tosoh Corporation).
[0049] The content (concentration) of the blocked isocyanate is preferably 0.5% by mass or more and 4% by mass or less, which is suitable for ensuring the adhesion of the formed conductive film to the substrate by generating intermolecular forces between the substrate and the like. If the content of the blocked isocyanate is less than 0.5% by mass, the adhesion between the formed conductive film and the substrate is not significantly improved, whereas if the content of the blocked isocyanate is more than 4% by mass, the amount of the isocyanate compound contained in the formed conductive film becomes too large, which may result in a decrease in conductivity.
[0050] <<Polyurethane>> As the polyurethane, for example, one obtained by reacting a known polyisocyanate with a known polyol can be used. The polyisocyanate is not particularly limited, and any known compound having two or more isocyanate groups can be used.
[0051] Specific examples of the polyisocyanate include aromatic isocyanates such as TDI (tolylene diisocyanate) based isocyanates, MDI (diphenylmethane diisocyanate) based isocyanates, XDI (xylylene diisocyanate) based isocyanates, NDI (naphthylene 1,5-diisocyanate) based isocyanates, and TMXDI (tetramethylene xylylene diisocyanate) based isocyanates; IPDI (isophorone diisocyanate); Alicyclic isocyanates such as H12MDI (hydrogenated MDI, dicyclohexylmethane diisocyanate) isocyanate and H6XDI (hydrogenated XDI) isocyanate, aliphatic isocyanates such as HDI (hexamethylene diisocyanate) isocyanate, DDI (dimer acid diisocyanate) isocyanate and NBDI (norbornene diisocyanate) isocyanate, etc. These isocyanates may be used alone or in combination of two or more types.
[0052] Specific examples of the polyol include polyether polyols such as polyoxyethylene glycol, polyoxypropylene glycol, and polyoxytetramethylene glycol, polyester polyols such as polyethylene adipate, polyethylene-butylene adipate, and polycaprolactone, acrylic polyols, polycarbonate polyols, polydimethylsiloxane-ethylene oxide adducts, polydimethylsiloxane-propylene oxide adducts, castor oil, etc. These polyols may be used alone or in combination of two or more.
[0053] As the polyurethane, it is preferable to use one having a polar group introduced therein, from the viewpoint of improving adhesion to the substrate. In addition, when using a polyurethane having a polar group introduced therein, it is expected that the flexibility of the conductive film formed can be increased and stress generated in the conductive film can be easily relieved. Examples of the polar group contained in the polyurethane include a carboxyl group, an amino group, a hydroxyl group, and a thiol group.
[0054] As the polyurethane, commercially available products can also be used. Examples of commercially available products include Nipporan 2304 (manufactured by Tosoh Corporation), Pandex T-5201, Pandex T-5205, Pandex T-5206, Pandex T-5210, Pandex T-5265L, and Pandex T-7170 (all manufactured by DIC Corporation), Byron UR1400, Byron UR3600, and Byron UR8300 (all manufactured by Toyobo Co., Ltd.), Diferamine MAU-4308HV, Diferamine MAU-5022, Diferamine MAU-8288A, and Diferamine MAU-9022 (all manufactured by Dainichi Seikagaku Co., Ltd.), MT Olestar NL2532, and MT Olestar NL2249E (all manufactured by Mitsui Chemicals, Inc.).
[0055] The content (concentration) of the polyurethane is preferably 0.5% by mass or more and 4% by mass or less, which is suitable for ensuring the adhesion of the formed conductive film to the substrate by generating intermolecular forces between the substrate and the like. If the content of the polyurethane is less than 0.5% by mass, the adhesion between the conductive film and the substrate is not significantly improved, whereas if the content of the polyurethane is more than 4% by mass, the conductive film contains too much polyurethane, which may result in low conductivity.
[0056] <Dispersion medium> The conductive ink may further contain a dispersion medium. As the solvent, for example, various highly polar solvents can be used. Examples of the highly polar solvent include methanol, ethanol, 1-propanol, isopropanol, 1-butanol, isobutanol, 2-butanol, tert-butanol, isoamyl alcohol, furfuryl alcohol, nitromethane, acetonitrile, pyridine, acetone cresol, dimethylformamide, dioxane, ethylene glycol, glycerin, phenol, p-cresol, propyl acetate, isopropyl acetate, 1-methoxy-2-propanol, 1- Examples of the alcohol include pentanol, 2-pentanol, 4-methyl-2-pentanol, 3-methyl-1-pentanol, 2-methyl-2,4-pentanediol, 3-methyl-2-pentanol, 1-hexanol, 2-hexanol, 2-pentanone, 2-heptanone, dipropylene glycol, 2-(2-ethoxyethoxy)ethyl acetate, 2-butoxyethyl acetate, 2-(2-butoxyethoxy)ethyl acetate, 2-methoxyethyl acetate, and 2-hexyloxyethanol. Among these, alcohols having 1 to 6 carbon atoms are preferred because it is easy to avoid attacking the substrate when the conductive ink is applied to the substrate. The above dispersion medium may be used alone or in combination of two or more kinds.
[0057] The dispersion medium preferably has a boiling point of at least 170° C. When the dispersion medium has a boiling point of at least 170° C., the conductive ink can be prevented from drying excessively after application and before the first baking.
[0058] The content (concentration) of the dispersion medium relative to the entire conductive ink is preferably 27% by mass or more and 79% by mass or less. If the concentration of the dispersion medium is 27% by mass or more, the conductive ink will not become too viscous and will be easy to handle.If the content of the dispersion medium is 79% by mass or less, the formed conductive film will tend to have sufficient conductivity.
[0059] The conductive ink may contain other components in addition to the fine silver particles, the amine, the polymer having an acidic group, the binder, and the dispersion medium, as long as the effects of the present invention are not impaired. Examples of the other components include a surfactant, an antifoaming agent, etc. Addition of a surfactant or an antifoaming agent makes it easier to form a uniform conductive film. The surfactant is not particularly limited, and anionic surfactants, cationic surfactants, and nonionic surfactants can be used.
[0060] In the conductive ink, the total amount of the silver particles, the amine, the polymer having an acidic group, the binder, and the dispersion medium is preferably 98% by mass or more, and more preferably 99% by mass, based on the entire conductive ink. The conductive ink may be composed of only silver particles, an amine, a polymer having an acidic group, a binder, and a dispersion medium.
[0061] In the conductive ink, the content of each of the constituent components can be measured, for example, by carrying out thermogravimetric analysis in which the temperature is raised from room temperature to 550° C. in the atmosphere.
[0062] Next, a method for producing the conductive ink will be described. The method for producing the conductive ink is not particularly limited, and examples thereof include the following methods. First, silver particles having an amine having a hydroxyl group and a polymer having an acidic group attached to the surface are prepared. The obtained silver particles are then dispersed in a dispersion medium together with a binder. Through these steps, the conductive ink is obtained. In the step of dispersing the silver particles in the dispersion medium, a dispersant may be added to the dispersion medium as necessary.
[0063] A method for producing silver microparticles having an amine having a hydroxyl group and a polymer having an acidic group attached to their surface includes, for example, a method comprising a first step of preparing a mixed solution of a silver compound that can be decomposed by reduction to produce silver, and a dispersant containing an amine and a polymer having an acidic group, and a second step of reducing the silver compound in the mixed solution to produce silver microparticles having an amine and a polymer having an acidic group attached to at least a portion of their surface. In addition, if an amine having a hydroxyl group is not mixed as the amine in the first step, an amine having a hydroxyl group is added after the second step and adhered to the surface of the silver particles.
[0064] In the first step, the total amount of amine added is preferably 2 mol or more per mol of silver atom. By adding 2 mol or more of amine per mol of silver atom, an appropriate amount of the amine can be attached to the surface of the silver fine particles generated by reduction, and the silver fine particles can be provided with excellent dispersibility in various dispersion media and low-temperature sinterability.
[0065] The amount of the polymer having an acidic group added in the first step is preferably 0.03 parts by mass or more and 0.2 parts by mass or less per part by mass of the silver compound. If the amount of the polymer having an acidic group added per part by mass of the silver compound is more than 0.2 parts by mass, the conductivity of the formed conductive film may deteriorate, and if it is less than 0.03 parts by mass, the effect of dispersing silver particles may not be obtained.
[0066] The composition of the mixed solution in the first step and the reduction conditions in the second step (e.g., heating temperature and heating time) are adjusted so that the particle size of the resulting silver particles is nanometer-sized. This causes a drop in the melting point of the silver particles, making low-temperature firing possible. The average primary particle size of the resulting silver particles is 10 nm or more and 30 nm or less.
[0067] A colloidal solution containing silver particles is obtained by carrying out the reduction reaction in the second step. After the reduction reaction, an amine may be added to adjust the composition of the colloidal solution. In addition to the silver particles, the colloidal solution contains dispersants (polymers having amines and acidic groups), and the electrolyte concentration of the entire solution tends to be high. In such a colloidal solution, the silver particles tend to coagulate and precipitate due to high electrical conductivity, etc. Therefore, it is preferable to carry out the next step of washing the colloidal solution to remove excess electrolyte.
[0068] As a method for washing the colloidal liquid, for example, the colloidal liquid may be left to stand for a certain period of time, the supernatant liquid may be removed, and then pure water or a lower alcohol (e.g., methanol) may be added and stirred, and the colloidal liquid may be further left to stand for a certain period of time and the supernatant liquid may be removed, and this process may be repeated several times. Other washing methods include, for example, a method of performing centrifugation instead of the above-mentioned standing, and a method of desalting using an ultrafiltration device, an ion exchange device, etc. Among these, the desalting method is preferable. The desalted liquid may be appropriately concentrated.
[0069] As the silver compound, various known silver compounds can be used, for example, silver salts or hydrates of silver salts can be used.Specific examples include silver salts such as silver nitrate, silver sulfate, silver chloride, silver oxide, silver acetate, silver oxalate, silver formate, silver nitrite, silver chlorate, and silver sulfide.These are not particularly limited as long as they are reducible, and may be dissolved in a suitable solvent or used as dispersed in the solvent.In addition, these may be used alone or in combination of two or more.
[0070] The silver compound is preferably silver oxalate. Silver oxalate is the simplest silver dicarboxylate, and the silver oxalate amine complex synthesized using silver oxalate is suitable for the synthesis of nanometer-sized silver particles because it undergoes reduction at low temperature and in a short time. Furthermore, when silver oxalate is used, no by-products are generated during synthesis, and only carbon dioxide derived from oxalate ions is generated outside the system, so there is little effort required for purification after synthesis.
[0071] The method of reducing the silver compound is preferably a heating method. The heating method is not particularly limited. The method of reducing the silver compound by heating includes, for example, a method of heating a complex compound generated from a silver compound such as silver oxalate and an amine, and decomposing a metal compound such as oxalate ion contained in the complex compound to generate atomic silver, which is aggregated. By the above method, silver fine particles having amine attached to the surface can be produced.
[0072] The particle size of the resulting silver microparticles can be controlled, for example, by adjusting the compounding ratio of the materials. In addition, when the silver compound is reduced by heating, the particle size can also be controlled by adjusting the heating conditions. Specifically, when synthesizing fine silver particles having an average primary particle size of 10 nm or more and 30 nm or less, the temperature rise rate during heating is preferably 5° C. / min or more and 30° C. / min or less. In this case, examples of the heating method include a method using a thermostatic bath, an oil bath, various heaters, a microwave, a hot plate, etc. The heating method is preferably a method that can control the heating conditions while actually measuring the temperature of the reaction solution. In addition, in order to stably produce silver fine particles having a predetermined particle size, the heating method is preferably a method that can set a temperature program.
[0073] Thus, in the metal amine complex decomposition method in which a complex compound of a silver compound is thermally decomposed in the presence of an amine to produce silver fine particles with an amine attached to the surface, atomic silver is generated by the decomposition reaction of a silver amine complex, which is a single type of molecule. Therefore, it is possible to generate atomic silver uniformly in the reaction system, and compared to the case in which silver atoms are generated by the reaction between multiple components, the non-uniformity of the reaction caused by composition fluctuations of the components that make up the reaction is suppressed, which is particularly advantageous when producing large amounts of silver powder on an industrial scale.
[0074] In addition, in the metal amine complex decomposition method, amine molecules are coordinated to the silver atoms produced, and it is presumed that the movement of the silver atoms during aggregation is controlled by the action of the amine molecules coordinated to the silver atoms. As a result, the metal amine complex decomposition method makes it possible to produce very fine metal particles (silver fine particles) with a narrow particle size distribution.
[0075] Furthermore, amine molecules are coordinately bonded to the surface of the produced silver particles, and these form a protective coating on the surface of the silver particles, making it possible to produce silver particles with excellent storage stability. Furthermore, since the amine molecules that form the protective coating can be easily eliminated by heating or the like, it is possible to produce fine silver particles that can be sintered at extremely low temperatures.
[0076] Next, the obtained silver particles are dispersed in a dispersion medium together with a binder to obtain the conductive ink. At this time, a dispersant may be added to the dispersion medium as necessary. Specifically, for example, the silver slurry obtained by washing the colloidal liquid containing the fine silver particles obtained in the second step is dispersed together with a binder in a dispersion medium such as an alcohol having 1 to 6 carbon atoms.
[0077] The method for dispersing the silver slurry and the binder in the dispersion medium is not particularly limited, and can be carried out by a conventionally known method using, for example, a mixer, a stirrer, etc. Alternatively, the mixture may be stirred with a spatula or the like, and an ultrasonic homogenizer with an appropriate output may be applied.
[0078] (How to use conductive ink) The conductive ink can be applied to a substrate and then baked to form a conductive film, and can therefore be suitably used in the fields of film devices and printed electronics. In particular, the method can be suitably used in a method for manufacturing a film device in which a step of applying a conductive ink to form electrical wiring is performed multiple times, in which a first firing is performed after each step of applying the conductive ink, and after the step of applying the conductive ink is performed multiple times, a second firing is performed to sufficiently sinter the silver microparticles. The conductive film can be used as wiring, electrodes, and the like for electronic circuit boards (for example, semiconductor integrated circuits), printed wiring boards, and thin film transistor substrates.
[0079] Examples of materials for the substrate include resin materials such as polycarbonate (PC), acrylonitrile-butadiene-styrene copolymer (ABS), acrylonitrile-styrene copolymer (AS), polypropylene (PP), polyethylene (PE), cycloolefin polymer (COP), polyamide (PA), polyacetal (POM), polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyphenylene sulfide (PPS), polyether ether ketone (PEEK), polystyrene (PS), polymethyl methacrylate (PMMA), polyphenylene ether (PPE), polysulfone (PSF), polyethersulfone (PES), polyamideimide (PAI), polyetherimide (PEI), polyimide (PI), and polyvinyl chloride (PVC). The material of the substrate may be, for example, an ink-absorbent material such as paper, fabric, porous ceramics, etc. Here, the ink-absorbent material means a material having a structure with an ink-receiving function. The above resin material is classified as an ink non-absorbent material.
[0080] The surface of the substrate may be provided with a surface layer (primer layer) for the purpose of enhancing adhesion to the conductive film, or may be subjected to a surface treatment such as hydrophilization treatment. Examples of the surface treatment method include dry treatments such as corona treatment, plasma treatment, UV treatment, and electron beam treatment.
[0081] The above-mentioned coating is a concept that includes both the case where the conductive ink is applied in a planar shape and the case where the conductive ink is applied (drawn) in a linear shape. The shape of the coating film (including the conductive film) may be planar, linear, or a combination of these. In addition, the coating film (conductive film) may be a continuous pattern, a discontinuous pattern, or a combination of these.
[0082] The method for applying the conductive ink is not particularly limited, and examples thereof include inkjet printing, screen printing, letterpress printing, intaglio printing, reverse printing, microcontact printing, dipping, spraying, bar coating, spin coating, dispenser method, casting, flexography, gravure, syringe method, and brush coating.
[0083] When the coating film of the conductive ink is baked at a first baking temperature (for example, 90° C. or higher and 120° C. or lower), adhesion between the coating film and the substrate is ensured. When the coating film of the conductive ink is baked at a second baking temperature (for example, 140° C. or higher), the conductivity of the conductive film is significantly improved. Note that the second baking temperature is preferably, for example, 160° C. or lower from the viewpoint of preventing heat damage to the substrate.
[0084] The first baking temperature is, for example, a temperature at which a portion of the amine having a hydroxyl group is removed. The second baking temperature is, for example, a temperature at which the protecting group of the blocked isocyanate dissociates or the polyurethane softens. Therefore, the first baking temperature may be set in consideration of the type of amine having a hydroxyl group, and the second baking temperature may be set in consideration of the type of binder.
[0085] The firing time of the first firing and the firing time of the second firing are not particularly limited, and may be appropriately set depending on the firing temperature. Heating conditions for the first and second baking can be selected, for example, by placing the material in an oven set to a predetermined temperature (e.g., 100°C or 150°C) or by raising the temperature from room temperature at a rate of 10°C / min and then maintaining the material at the predetermined temperature. The heating method in the first baking and the second baking is not particularly limited, and examples thereof include methods using a conventionally known constant temperature dryer, reflow furnace, or the like.
[0086] The conductive film has a thickness of, for example, 0.1 μm to 5 μm, and preferably 0.2 μm to 3 μm.The conductive film has a volume resistivity of, for example, 40 μΩ·cm or less. EXAMPLES
[0087] Hereinafter, the embodiments of the present invention will be described in more detail with reference to examples, but the embodiments of the present invention are not limited to the following examples.
[0088] The binders used in the examples and comparative examples are as follows. (binder) (1) Duranate E402-B80B (manufactured by Asahi Kasei Corporation): Contains about 80% by mass of blocked hexamethylene diisocyanate, which is a blocked isocyanate. The blocking agent is methyl ethyl ketone oxime. The dissociation temperature of the protecting group is 130°C. (2) Takenate B-890 (manufactured by Mitsui Chemicals): Contains about 60% by mass of blocked xylylene diisocyanate, which is a blocked isocyanate. The dissociation temperature of the protecting group is 150°C. (3) Diferamine MAU-8288A (manufactured by Dainichiseika Chemicals Mfg. Co., Ltd.): A polycarbonate-based polyurethane resin with a weight-average molecular weight of 50,000. (4) EPICLON 850 (manufactured by DIC): a bisphenol A type epoxy resin.
[0089] Example 1 1g of DISPERBYK-118 (Big Chemie Japan) and 100g of 2-(2-aminoethoxy)ethanol (Fujifilm Wako Pure Chemical Industries) were weighed into a 10L glass container and thoroughly mixed. 30g of silver oxalate (Toyo Kagaku Kogyo) was added and further mixed to obtain a viscous substance. The obtained viscous substance was heated to 100°C for 5 minutes to allow the reduction reaction to proceed. After the reduction reaction, 100 ml of methanol (manufactured by Fujifilm Wako Pure Chemical Industries) was added to the reaction solution, which was then stirred and centrifuged twice to remove excess organic components. This was then dried for 20 minutes, after which 30 g of dispersion medium was added. As the dispersion medium, 15 g of dipropylene glycol (manufactured by Fujifilm Wako Pure Chemical Industries) and 15 g of 4-methyl-2-pentanol (manufactured by Fujifilm Wako Pure Chemical Industries) were used. After stirring to disperse the silver particles, the mixture was centrifuged to remove coarse particles, and the supernatant was collected. 0.7 g of Duranate E402-B80B was added to the supernatant and stirred to obtain conductive ink 1.
[0090] Example 2 1 g of DISPERBYK-102 (Big Chemie Japan), 80 g of 3-methoxypropylamine (Tokyo Chemical Industry Co., Ltd.), and 100 g of 2-(2-butoxyethoxy)ethyl acetate (Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed into a 10 L glass container and mixed thoroughly. 30g of silver oxalate was added and further stirred to obtain a viscous substance. The obtained viscous substance was heated to 100°C for 5 minutes to allow the reduction reaction to proceed. Then, 85g of 2-(2-aminoethoxy)ethanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added and stirred for 10 minutes. 100ml of methanol was further added to the reaction solution to which 2-(2-aminoethoxy)ethanol had been added, stirred, and centrifuged twice to remove excess organic components. After drying for 20 minutes, 30g of dispersion medium was added. As the dispersion medium, 15g of 2-methyl-2,4-pentanediol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 15g of 4-methyl-2-pentanol were used. After stirring and dispersing the silver fine particles, the mixture was centrifuged to remove coarse particles, and the supernatant was collected. 0.7g of Duranate E402-B80B was added to the supernatant and stirred to obtain conductive ink 2.
[0091] Example 3 Conductive ink 3 was obtained in the same manner as in Example 2, except that the amount of DISPERBYK-102 was changed to 2 g, and 80 g of 3-methoxypropylamine was changed to 68 g of 3-ethoxypropylamine (manufactured by Tokyo Chemical Industry Co., Ltd.).
[0092] Example 4 Conductive ink 4 was obtained in the same manner as in Example 2, except that 0.7 g of Duranate E402-B80B was changed to 1.0 g of Takenate B-890, and 4-methyl-2-pentanol was changed to 2-butoxyethanol.
[0093] Example 5 Conductive ink 5 was obtained in the same manner as in Example 3, except that 0.7 g of Duranate E402-B80B was changed to 1.5 g of Diferamine MAU-8288A.
[0094] Example 6 Conductive ink 6 was obtained in the same manner as in Example 2, except that 2-(2-aminoethoxy)ethanol was changed to 2-(2-aminoethylamino)ethanol (manufactured by Tokyo Chemical Industry Co., Ltd.).
[0095] Example 7 Conductive ink 7 was obtained in the same manner as in Example 1, except that the amount of each dispersion medium (dipropylene glycol and 4-methyl-2-pentanol) was changed from 15 g to 5 g.
[0096] Comparative Example 1 Conductive ink 8 was obtained in the same manner as in Example 1, except that the amount of 2-(2-aminoethoxy)ethanol was changed to 150 g.
[0097] Comparative Example 2 Conductive ink 9 was obtained in the same manner as in Example 1, except that 0.7 g of Duranate E402-B80B was changed to 0.5 g of EPICLON 850 (manufactured by DIC).
[0098] Comparative Example 3 A conductive ink 10 was obtained in the same manner as in Example 2, except that 2-(2-aminoethoxy)ethanol was not added.
[0099] Comparative Example 4 Conductive ink 11 was obtained in the same manner as in Example 2, except that no binder was added.
[0100] Comparative Example 5 Conductive ink 12 was obtained in the same manner as in Example 6, except that 65 g of 2-butoxyethanol was further added as a dispersion medium.
[0101] Comparative Example 6 An attempt was made to obtain a conductive ink in the same manner as in Example 2, except that DISPERBYK-102 was not added. However, the dispersion of the silver particles in the dispersion medium was poor, and the ink could not be recovered.
[0102] Comparative Example 7 An attempt was made to obtain a conductive ink in the same manner as in Example 1, except that DISPERBYK-118 was changed to DISPERBYK2155 (manufactured by Big Chemie Japan), which is a polymer having no acidic group and has a basic group. However, the dispersibility of the silver particles in the dispersion medium was poor, and the ink could not be recovered.
[0103] <Evaluation> The average primary particle size and the concentration of the silver particles contained in the conductive ink were measured. Furthermore, evaluation samples were prepared and then subjected to various evaluations. The results are shown in Tables 1 and 2.
[0104] (Particle size measurement) The conductive inks prepared in the examples and comparative examples were observed for silver microparticles at a magnification of 200,000 times using a scanning electron microscope (Hitachi S-4800 model), and the particle diameters of the microparticles contained in the captured images were measured using image analysis software WinROOF (MITANI CORPORATION), and the number average particle diameter was calculated as the average primary particle diameter.
[0105] (Measurement of silver particle concentration) The concentration of silver particles contained in the conductive inks prepared in the examples and comparative examples was measured by the following method. Using a differential thermobalance TG-DTA8122 (Rigaku), thermogravimetric analysis was performed by increasing the temperature from room temperature to 550°C at a rate of 10°C / min in air. The residue at 550°C was taken as the silver particle concentration.
[0106] (Preparation of evaluation samples) The conductive inks prepared in the examples and comparative examples were applied to a 30 mm x 30 mm PET film (thickness 50 μm) as a substrate using a spin coater at 500 rpm x 20 sec. Then, the film was baked for 30 minutes in a constant temperature dryer set at 100°C (first baking). Then, the film was baked for 30 minutes in a constant temperature dryer set at 150°C (second baking). The thickness of the obtained conductive coating after the second baking was approximately 1.0 μm. The evaluation of (1) electrical conductivity and (2) adhesion described below were carried out on the coating film after the first baking and the coating film after the second baking.
[0107] (1) Conductivity evaluation The surface resistance of the evaluation sample was measured using a Loresta (MCP-T610, manufactured by Nitto Seiko Analytech). The film thickness was also measured using a laser microscope (VK-X150, manufactured by KEYENCE). The volume resistance was calculated from the measurement results. The conductivity of the coating film (conductive film) formed after the second baking was also evaluated according to the following criteria. A: Less than 25μΩ·cm B: 25μΩ·cm or more and 40μΩ·cm or less C: More than 40 μΩ cm
[0108] (2) Evaluation of adhesion Adhesion evaluation was performed using cross-cuts according to ASTM D3359-09. That is, 25 grids of 1 mm width were created on the evaluation sample with a cutter, cellophane tape (CT-24, manufactured by Nichiban, 24 mm wide) was adhered to the grids with finger pressure, and the tape was peeled off in one go at an angle of approximately 60° from one end. The results were evaluated according to the following criteria. A: Peeling rate is less than 5% B: Peeling rate is 5% to 15% C: Peeling rate is over 15%
[0109] (3) Overall evaluation Based on the results of three items, adhesion after the first firing, volume resistivity after the second firing, and adhesion after the second firing, an overall judgment was made according to the following criteria. A: All three items are evaluated B: At least one B out of three items and no C C: Any of the three items is rated C
[0110] [Table 1]
[0111] [Table 2]
Claims
1. A conductive ink comprising silver particles, an amine, a polymer having an acidic group, and a binder, Further, the dispersion medium is included, The average primary particle diameter of the silver fine particles is 10 nm or more and 30 nm or less, The content of the silver fine particles is 20% by mass or more and 65% by mass or less, The amine includes an amine having a hydroxyl group, The binder includes a blocked isocyanate and / or a polyurethane, A conductive ink, in which the total amount of silver particles, amine, polymer having an acidic group, blocked isocyanate, polyurethane, and dispersion medium is 98 mass % or more relative to the entire conductive ink.
2. 2. The conductive ink according to claim 1, wherein the amine having a hydroxyl group comprises at least one selected from the group consisting of 2-(2-aminoethoxy)ethanol, 2-(2-aminoethylamino)ethanol, 2-[2-(2-aminoethoxy)ethoxy]ethanol, and monoethanolamine.
3. The conductive ink according to claim 1 or 2, further comprising an alkoxyamine as the amine.
4. The binder comprises a blocked isocyanate, The conductive ink according to claim 1 , wherein the concentration of the blocked isocyanate is 0.5% by mass or more and 4% by mass or less.
Citation Information
Patent Citations
Production for colloid of noble metal or copper
JP1999319538A
Conductive paste
JP2003223812A
Conductive silver paste and electromagnetic wave shielding member using it
JP2005294254A
Silver particulate, method for producing the same and conductive paste containing silver particulate
JP2006183072A
Metallic particle paste and method for manufacturing conductive substrate
JP2010153118A